A Defined α‐Helix in the Bifunctional O‐Glycosylated Natriuretic Peptide TcNPa from the Venom of Tropidechis carinatus1. Issue 16 (3rd March 2015) - Reeks, Timothy; Jones, Alun; Brust, Andreas; Sridharan, Sindhuja; Corcilius, Leo; Wilkinson, Brendan L.; Thaysen‐Andersen, Morten; Payne, Richard J.; Kini, R. Manjunatha; Daly, Norelle L.; Alewood, Paul F.
Abstract Natriuretic peptides (NP) play important roles in human cardiac physiology through their guanylyl cyclase receptors NPR‐A and NPR‐B. Described herein is a bifunctional O‐glycosylated natriuretic peptide, TcNPa, from Tropidechis carinatus venom and it unusually targets both NPR‐A and NPR‐B. Characterization using specific glycosidases and ETD‐MS identified the glycan as galactosyl‐β(1‐3)‐N‐acetylgalactosamine (Gal‐GalNAc) and was α‐linked to the C‐terminal threonine residue. TcNPa contains the characteristic NP 17‐membered disulfide ring with conserved phenylalanine and arginine residues. Both glycosylated and nonglycosylated forms were synthesized by Fmoc solid‐phase peptide synthesis and NMR analysis identified an α‐helix within the disulfide ring containing the putative pharmacophore for NPR‐A. Surprisingly, both forms activated NPR‐A and NPR‐B and were relatively resistant towards proteolytic degradation in plasma. This work will underpin the future development of bifunctional NP peptide mimetics.